Influence of Stress on Blood Morphology - N. Shulga, Nikolay; M. Mandro, Nikolay; A. Gavrilova, Galina; N. Chubin, Alexey; Yu. Sayapina, Irina; A. Gavrilov, Yuriy; V. Hibchenov, Lopsondorzho; V. Trush, Natal'ya (International Journal of Engineering and Technology, 2018)
Stress is a set of nonspecific changes in the body that are the result of its neurohumoral reaction to external stimuli, and its causative factors are called stressors. Changes in the body caused by a stressor are called the general adaptation syndrome, which is actually the clinical manifestation of stress. Various stresses (technological, temperature, rank ones, trauma, burns, etc.) should be considered as conditions that lead to a decrease in the level of the body's immune status and an increase in the susceptibility of animals to pathogenic and potentially pathogenic microflora that is constantly persistent in their bodies and the surrounding environment. This pattern is manifested in varying degrees in farms of different forms of ownership, in the form of stress factors that reduce the level of the immune status of the organism. The article presents the results of research on the influence of stress of regrouping on blood morphology and the immune system of newborn calves. Calves’ blood was examined before and after regrouping, it was found that a decrease in the level of the immune status of the organism manifesting itself in a change in the morphological blood pattern and an increase in the susceptibility of animals to diseases, is caused by stress of regrouping, thus, stress negatively affects the overall parameters of blood morphology and calves’ immunity.